Diagnosis, results, and nursing interventions for patients with acute renal injury - Grassi, Mariana de Freitas [UNESP]; Queiroz Dell'Acqua, Magda Cristina [UNESP]; Jensen, Rodrigo [UNESP]; Bertoncello Fontes, Cassiana Mendes [UNESP]; Carvalho Passos Guimaraes, Heloisa Cristina Quatrini (Univ Fed Sao Paulo, Dept Enfermagen, 2017)
Objective: To identify prevalence and correlate diagnosis, results, and nursing interventions in patients with acute renal injury (ARI) who were hospitalized in an intensive care unit (ICU). Methods: This was a cross-sectional study including 98 patients older than 18 years old with ARI who were undergoing hemodialysis treatment in the ICU. The study was carried out in an ICU a large public hospital located in the city of Sao Paulo, Brazil. For statistics analysis we used the SPSS v21.0 to estimate prevalence, the 95% of confidence interval and sample error of 0.05. Data were collected from March to July 2016 using structured interviews, anamnesis and physical exam of patients using an instrument designed by this study researchers. The main instrument was completed by the principal researcher. Nursing consultation lasted for approximately 30 minutes. Of the total sample, 10% was selected and checked randomly in order to evaluate data quality and atypical values. Two patients previously did a pilot test to verify whether information in the instrument achieved the objective of the study. Results: The 98 participatns were aged >= 60 years (33%), men (60%), and classified as pre-renal injury (54%). Prevalent diagnosis was (100%) risk of infection, risk of inefficient gastrointestinal perfusion, risk of ineffective renal perfusion, risk of electrolyte imbalance, excessive fluid volume, and risk of imbalanced fluid volume. Results (100%) were: severity of infection, access for hemodialysis, tissue perfusion abdominal organs, hydric balance, mobility, removal of toxins and renal function. Prevalent nursing interventions (100%) were: promotion against infection, control of infection, maintenance of access for dialysis, hydroeletrolitic control, urinary elimination control, acid-base control, electrolytic control, hypervolemia control, hydric control, hydric monitoring, respiratory physiotherapy, respiratory and positioning monitoring. Correlations were significant (p<0.001) between diagnosis and nursing interventions and between nursing interventions and results. Conclusion: Main diagnosis, results and nursing interventions related with loss of renal function originated from changes of renal perfusion, volemia, hydroelectrolytic dysfunctions, and risk of infection. The number of diagnosis showed to be correlated with number of nursing interventions and nursing interventions was correlated with results.
Keywords: Nursing diagnosis; Nursing process; Acute kidney injury; Renal dialysis; Critical care